Personal Responsibility Relationship to Behavior Environmental Responsibility Behaviour - Yulistiana Yulistiana; Agung Purwanto; Achmad Husen (Eduvest - Journal of Universal Studies, 2022)
This study aims to determine the relationship between the Personal Responsibility variable and the Environmental Responsibility Behavior variable at BAPPEDA Kebumen Regency. The selected sample is 52 people with the criteria of civil servants and non civil servants. This research uses survey method. The results of this study conclude that 1) The results of the calculation of the normality of the estimated Y-X2 error obtained Lo = 0.043, while Lt = 0.074. 2) Homogeneity test obtained 2count < 2table or 48.952 <124. 3) There is a positive relationship between Personal Responsibility and environmental responsibility behavior with the regression equation = 37.52 + 0.74X2 with R = 54%,